Migration and livelihood during Covid pandemic in India - Satyendra Singh Narwaria, (National Geographical Journal of India, 2021)
A nationwide lockdown was announced on 24 March 2020 as a strategy to contain the spread of the corona virus; the citizens of the country had little idea of what they would have to endure in the days ahead. Heart-wrenching images of migrants and trying to get back to their villages received attention and criticism. This article attempts to identify the problems to address the challenges so that the effect of pandemics in future can be better tackled and build surge capacity to deal with a crisis.